If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + ln(x + 1) = ln(x + -1) Reorder the terms: 1 + ln(1 + x) = ln(x + -1) 1 + (1 * ln + x * ln) = ln(x + -1) 1 + (1ln + lnx) = ln(x + -1) Reorder the terms: 1 + 1ln + lnx = ln(-1 + x) 1 + 1ln + lnx = (-1 * ln + x * ln) 1 + 1ln + lnx = (-1ln + lnx) Add '-1lnx' to each side of the equation. 1 + 1ln + lnx + -1lnx = -1ln + lnx + -1lnx Combine like terms: lnx + -1lnx = 0 1 + 1ln + 0 = -1ln + lnx + -1lnx 1 + 1ln = -1ln + lnx + -1lnx Combine like terms: lnx + -1lnx = 0 1 + 1ln = -1ln + 0 1 + 1ln = -1ln Solving 1 + 1ln = -1ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add 'ln' to each side of the equation. 1 + 1ln + ln = -1ln + ln Combine like terms: 1ln + ln = 2ln 1 + 2ln = -1ln + ln Combine like terms: -1ln + ln = 0 1 + 2ln = 0 Add '-1' to each side of the equation. 1 + -1 + 2ln = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2ln = 0 + -1 2ln = 0 + -1 Combine like terms: 0 + -1 = -1 2ln = -1 Divide each side by '2n'. l = -0.5n-1 Simplifying l = -0.5n-1
| 15x-4.9x^2=-30 | | 2x-7y=3xk | | -0.666666666666667(5p-16)=10 | | .5(7a+1)=18 | | 2(7a+1)=18 | | 10(a+1)-14a=9-(4a-1) | | 2(8x-1)=6(5-x) | | 3x+125=11x-11 | | 5x+2+3x=8x | | 175-2x=34x+15 | | 2x+12=-76-9x | | 128-4x=4x+24 | | 3c-5+2c-11=9 | | 6x+14=102-5x | | x-17=48 | | 9+12x=75+x | | 8x+1=6x-13 | | 3x+33=11x-63 | | -8(-8k-6)=6x-22 | | 79-5x=22x+22 | | 12-10x=92-45x | | 180-(x-20)=3x | | q=4p-11 | | 157-5x=5x+17 | | 92-4x=10x+22 | | y=y+12 | | 2x+11=53-4x | | -8-x=-3.5x+5 | | 2x-1+1=4 | | 5x-8=3x+4 | | 4.2x+4.4=3.1x | | 2x+9=x+5 |